Pre-pubertal growth and cognitive function. Issue 1 (20th December 2005) - Montgomery, S M; Ehlin, A; Sacker, A
Abstract : British longitudinal data were used to investigate the association of heights at 22 months and 5 years with a digit recall test at age 10 years. Greater height, particularly at 5 years, was associated with higher scores, suggesting that some exposures influence both growth and capability for cognitive function.